2013
DOI: 10.1056/nejmoa1213096
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*13:01and the Dapsone Hypersensitivity Syndrome

Abstract: HLA-B*13:01 was associated with the development of the dapsone hypersensitivity syndrome among patients with leprosy. (Funded by the National Natural Science Foundation of China and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
225
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(244 citation statements)
references
References 24 publications
10
225
2
7
Order By: Relevance
“…Randomized, controlled trial of TNF-α antagonist in CTL-mediated severe cutaneous adverse reactions Chuang-Wei Wang, 1,2 Lan-Yan Yang, 3 Chun-Bing Chen, 1 Hsin-Chun Ho, 1,4 Shuen-Iu Hung, 5 Chih-Hsun Yang, 1,4 Chee-Jen Chang, 6,7 Shih-Chi Su, 1,8 Rosaline Chung-Yee Hui, 1,4 See-Wen Chin, 1 Li-Fang Huang, 3 Yang Yu-Wei Lin, 1 Wei-Yang Chang, 3 Wen-Lang Fan, 8 Chin-Yi Yang, 1 Ji-Chen Ho, 4,9 Ya-Ching Chang, 1,4 Chun-Wei Lu, 1,4 Wen-Hung Chung, 1,2,4,8 and the Taiwan Severe Cutaneous Adverse Reaction (TSCAR) Consortium…”
Section: Funding Ministry Of Science and Technology Of Taiwanmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized, controlled trial of TNF-α antagonist in CTL-mediated severe cutaneous adverse reactions Chuang-Wei Wang, 1,2 Lan-Yan Yang, 3 Chun-Bing Chen, 1 Hsin-Chun Ho, 1,4 Shuen-Iu Hung, 5 Chih-Hsun Yang, 1,4 Chee-Jen Chang, 6,7 Shih-Chi Su, 1,8 Rosaline Chung-Yee Hui, 1,4 See-Wen Chin, 1 Li-Fang Huang, 3 Yang Yu-Wei Lin, 1 Wei-Yang Chang, 3 Wen-Lang Fan, 8 Chin-Yi Yang, 1 Ji-Chen Ho, 4,9 Ya-Ching Chang, 1,4 Chun-Wei Lu, 1,4 Wen-Hung Chung, 1,2,4,8 and the Taiwan Severe Cutaneous Adverse Reaction (TSCAR) Consortium…”
Section: Funding Ministry Of Science and Technology Of Taiwanmentioning
confidence: 99%
“…A detailed study profile is shown in Figure 2. We determined whether the enrolled participants had SJS-TEN using the Registry of Severe Cutaneous Adverse ReacOver the past 2 decades, studies have shown that the pathomechanism of SJS-TEN is associated with the effector cytotoxic T lymphocytes (CTLs) that recognize culprit drugs presented by HLA class I molecules on keratinocytes (6)(7)(8)(9) (8,10,11). We have previously identified secretory granulysin as a key mediator that leads to disseminated keratinocyte apoptosis and detachment of the epidermis and mucous membranes in SJS-TEN (12,13).…”
Section: Preclinical Testing Of Etanercept: Ex Vivo Testing For Potenmentioning
confidence: 99%
“…Genetic factors appear to play in role in the predisposition of drug allergy. Certain HLA types such as HLA-B*13:01 and the dapsone hypersensitivity syndrome [19], HLA B*1502 associated with carbamazepine induced SJS/TEN in Han Chinese in Taiwan and Indians [20][21][22] and HLA A* 31:01 in Japanese and Europeans [23,24].…”
Section: Risk Factors For Drug Allergymentioning
confidence: 99%
“…Nomenclature for severe drug-induced cutaneous adverse reactions with systemic symptoms is variable and includes the following terms: drug hypersensitivity syndrome, hypersensitivity syndrome, drug reaction with eosinophilia and systemic symptoms. Organ-specific toxicities such as drug-induced myotoxicity, liver injury, agranulocytosis, kidney or pancreas injury can also include immunological etiology as demonstrated by clinical phenotype characteristics and significant associations with genes with immune function within the MHC on chromosome 6, primarily HLA genes [2][3][4][5][6][7].Pathophysiological mechanisms of immune ADRs are not fully understood, however, there are three recognized models that explain T-cell-mediated hypersensitivity [8]. They include: hapten/prohapten model (drug example -sulfamethoxazole), where a small drug or its reactive metabolite induces an immune response by covalently binding to an endogenous protein to become immunogenic and is then presented on an MHC molecule to a T-cell receptor; the pharmacological interactions (p-i) model proposes that a drug can bind directly to the T-cell receptor or MHC molecule and stimulate T cells directly, independent of antigen processing (drug examplecarbamazepine); and the altered repertoire model, where a drug binds noncovalently in a concentration-dependent manner to the peptide binding groove of the HLA molecule and changes the chemistry of the HLA molecule that displays altered self-peptides which are recognized by T cells (drug example -abacavir).…”
mentioning
confidence: 99%
“…Nomenclature for severe drug-induced cutaneous adverse reactions with systemic symptoms is variable and includes the following terms: drug hypersensitivity syndrome, hypersensitivity syndrome, drug reaction with eosinophilia and systemic symptoms. Organ-specific toxicities such as drug-induced myotoxicity, liver injury, agranulocytosis, kidney or pancreas injury can also include immunological etiology as demonstrated by clinical phenotype characteristics and significant associations with genes with immune function within the MHC on chromosome 6, primarily HLA genes [2][3][4][5][6][7].…”
mentioning
confidence: 99%